Internalisasi Nilai Spiritual Melalui Layanan Bimbingan Dan Konseling: Upaya Penguatan Kejujuran Akademik Siswa. - Pratama, Sandi; Sultan, Azzahrah Mumtazah; Novitasari, Rifani; Niswa, Niswa; Aemi, Nur (Institut Agama Islam Negeri Parepare, 2024)
Internalization of spiritual values ​​is the process of instilling and integrating values ​​derived from spiritual teachings into an individual's self, thus becoming part of their daily thought patterns, attitudes, and behaviors. In the educational context, low academic honesty, such as cheating, plagiarism, and assignment manipulation, indicates an integrity crisis that cannot be addressed solely through rules and sanctions. Therefore, Guidance and Counseling (BK) has a strategic role in developing an approach that is not only oriented towards cognitive aspects but also touches on the affective and spiritual dimensions of students. This study uses a qualitative method with a literature study approach (library research), namely by analyzing various scientific sources such as books, journals, and previous research results relevant to the concept of internalizing spiritual values, BK services, and academic honesty. This study focuses on how the process of internalizing spiritual values ​​can be integrated into BK services as a preventive measure and character development. The results of the study indicate that internalization of spiritual values ​​in BK can be carried out through the stages of understanding values, appreciating meaning, habituating behavior, and self-reflection. Values ​​such as honesty, responsibility, trustworthiness, and integrity are instilled through individual counseling, group guidance, and classical services that emphasize intrinsic moral awareness. A spiritual approach helps students recognize that honesty is not merely an academic obligation, but rather a moral commitment aligned with their beliefs and the meaning of life. Thus, internalizing spiritual values ​​through guidance and counseling is an effective and sustainable strategy for enhancing academic honesty and developing students' character with integrity